Pulmonary embolism in COVID-19 patients: a French multicentre cohort study. (13th July 2020) - Fauvel, Charles; Weizman, Orianne; Trimaille, Antonin; Mika, Delphine; Pommier, Thibaut; Pace, Nathalie; Douair, Amine; Barbin, Eva; Fraix, Antoine; Bouchot, Océane; Benmansour, Othmane; Godeau, Guillaume; et al.
Abstract: Aims: While pulmonary embolism (PE) appears to be a major issue in COVID-19, data remain sparse. We aimed to describe the risk factors and baseline characteristics of patients with PE in a cohort of COVID-19 patients. Methods and results: In a retrospective multicentre observational study, we included consecutive patients hospitalized for COVID-19. Patients without computed tomography pulmonary angiography (CTPA)-proven PE diagnosis and those who were directly admitted to an intensive care unit (ICU) were excluded. Among 1240 patients (58.1% men, mean age 64 ± 17 years), 103 (8.3%) patients had PE confirmed by CTPA. The ICU transfer and mechanical ventilation were significantly higher in the PE group (for both P < 0.001). In an univariable analysis, traditional venous thrombo-embolic risk factors were not associated with PE ( P > 0.05), while patients under therapeutic dose anticoagulation before hospitalization or prophylactic dose anticoagulation introduced during hospitalization had lower PE occurrence [odds ratio (OR) 0.40, 95% confidence interval (CI) 0.14–0.91, P = 0.04; and OR 0.11, 95% CI 0.06–0.18, P < 0.001, respectively]. In a multivariable analysis, the following variables, also statistically significant in univariable analysis, were associated with PE: male gender (OR 1.03, 95% CI 1.003–1.069, P = 0.04), anticoagulation with a prophylactic dose (OR 0.83, 95% CI 0.79–0.85, P < 0.001) or a therapeutic dose (OR 0.87, 95% CI 0.82–0.92, P < 0.001), C-reactive protein (OR 1.03, 95% CI 1.01–1.04, P = 0.001), and time from symptom onset to hospitalization (OR 1.02, 95% CI 1.006–1.038, P = 0.002). Conclusion: PE risk factors in the COVID-19 context do not include traditional thrombo-embolic risk factors but rather independent clinical and biological findings at admission, including a major contribution to inflammation. Graphical Abstract: Audio Abstract: